Correction to: Beta alanine supplementation effects on metabolic contribution and swimming performance - Matheus Silva Norberto; Ricardo Augusto Barbieri; Danilo Rodrigues Bertucci; Ronaldo Bucken Gobbi; Eduardo Zapaterra Campos; Alessandro Moura Zagatto; Ellen Cristini De Freitas; Marcelo Papoti (Taylor & Francis Group, 2020)
An amendment to this paper has been published and can be accessed via the original article.